Academic neurosurgery in the UK: present and future directions. Issue 1128 (20th August 2019) - Waqar, Mueez; Davies, Benjamin M; Zakaria, Rasheed; Barone, Damiano G; Kolias, Angelos G; Yu, Kenny K; Ellenbogen, Jonathan R; Brennan, Paul M; Kotter, Mark RN; Gray, William P; King, Andrew T; Turner, Carole; et al.
Abstract: Academic neurosurgery encompasses basic science and clinical research efforts to better understand and treat diseases of relevance to neurosurgical practice, with the overall aim of improving treatment and outcome for patients. In this article, we provide an overview of the current and future directions of British academic neurosurgery. Training pathways are considered together with personal accounts of experiences of structured integrated clinical academic training and unstructured academic training. Life as an academic consultant is also described. Funding is explored, for the specialty as a whole and at the individual level. UK academic neurosurgical organisations are highlighted. Finally, the UK's international standing is considered.